SEBARAN SPASIAL LAHAN KRITIS UNTUK PRIORITAS REHABILITASI BERBASIS SISTEM INFORMASI GEOGRAFIS DAN PENGINDERAAN JAUH DI DAS JUWANA HULU MURIA (Geo-Image, 2016)
This study purposed to know the spatial distribution of critical land, to knowarea of rehabilitation priority and to present information of rehabilitation prioritycritical land area. This research method is quantitative descriptive. Data analysistechniques in this study is scoring and overlay. The preparation of the technicalguidelines of spatial data critical land based on the Regulation DG WatershedManagement and Forestry Social Number: P.4 / V-SET / 2013. The results showthere are several level of critical land distribution; rather critical of 2.201 hectares,a critical of 135 hectares and is very critical of 2.3 hectares. Areas ofrehabilitation priority at the study site, the first priority area of 247 hectares, thesecond priority area of 137 hectares and not a priority 2.201 hectares. Presentationof rehabilitation priority critical land information its hope can help the process ofmonitoring the presence of critical land and to direct area of rehabilitation priority.